Optimizing accounting education through artificial intelligence powered mobile apps - Ei Myo, Thant Zin; Myat Pan, Hmone Thin; Hein Linn, Htet; Syukur, Muhammad (Faculty of Accountancy, Universiti Teknologi MARA (UiTM) Cawangan Kelantan, 2025)
Accounting subjects are generally considered difficult because of their abstract theoretical concepts and the excessive use of quantitative analysis, which may cause cognitive overload and a lack of interest from students. In order to solve these problems, this project presents a mobile application based on artificial intelligence (AI) that aims to transform accounting education. The app provides AI-assisted tutoring, personalized learning tracks, interactive quizzes, and entertaining educational videos according to every student's learning speed, taste, and level of knowledge. Using the gamification features such as points, badges, and leaderboards, the platform increases motivation, enhances memory retention, and promotes consistent learning habits. In addition, it connects the knowledge gap between theory and practice by using real-world case simulations and scenario-based learning activities. Such features enable students to use the principles of accounting in a dynamic, practical manner. Finally, the app provides content in an easy-to-understand, flexible, and entertaining way. It seeks to enhance academic achievement, increase confidence, and change how students view and interact with accounting.